Implementation Docker and Kubernetes Scaling Using Horizontal Scaler Method for Wordpress Services - Suryayusra; Destarina, Nova; Negara, Edi Surya; Supratman, Edi; Ulfa, Maria (Sinkron : jurnal dan penelitian teknik informatika, 2024)
Container is a technology that has recently been widely used because of the additional features that are very easy and convenient to use, especially for web hosting service developers, with Container making it easier for system admins to manage applications including building, processing and running applications on Container. With Container the process of creating and using the system will be easier but along with too many user requests so that the service does not run optimally. Therefore, the Container must have good scalability and performance. Scalability is needed for systems that can adjust to the needs of user demand and performance is needed to maintain the quality of services provided. This research aims to implement scaling using Docker and Kubernetes in terms of scalability and performance. The parameters of comparison between Docker and Kubernetes are for scalability, scaling up and scaling down time and for performance. The method in this research uses the Action Research methodology, which is a research model that is simultaneously practiced and theorized. With the initial steps of problem identification, action planning, action implementation, observation and evaluation. Based on the results that have been obtained, Docker consumes more CPU & Memory Usage Resources, namely at 500 Users Kubernetes consumes Resources with an average of 94.47%-4.70% while in Kubernetes 89.11%-4.50 because in Kubernetes itself has a complex system, especially special component components such as APIs, Metrics Server, Kubernetes manager to run the Container. While in Docker only has Docker Manager and Docker Compose components.